STUDY OF GEOLOGICAL CONDITION OF MELUKOTE REGION FOR FINDING THE SUITABILITY OF MINERALS AND ROCKS FOR CONSTRUCTION AND FINDING ECONOMICAL MINERALS - Rani, Babitha; Avinash; Aravind; Rohit; Dinakar, Raghavendra Prasad; Ramesh; Raghu (International Journal of Research -GRANTHAALAYAH, 2017)
A study was carried out to understand the geological condition in and around MELUKOTE region. THE MELUKOTE located in Mandya district, Karnataka. During the geological survey we have found different minerals and rocks such as Gneiss, foliated and non-foliated rocks, foliated schist, sedimentary rock (Breccia), metamorphic rocks, mica sheets, mica schist, pink granite gneiss rock, Biotite, muscovite, sillimanite. The samples collected were analyzed for various physical properties that is form, colour, streak, lustre, cleavage, fracture, hardness, specific gravity, chemical composition. Among all these minerals quartzite and mica minerals are abundant and can be extracted economically. The rocks undergone physical, chemical, biological, weathering. Chemical weathering processes are among the most fundamental natural processes operating at and near the surfaces of earth [1]. These rocks are not suitable for construction. By the study of pediments near the new tank project, shows that Kaveri river is dried.